Semantic errors in the subtitle translation of TED Talk “How Books Can Open Your Mind” - Suryani, Suryani; Basith, Rayhan Izzati; Tathahira, Tathahira (Accentia: Journal of English Language and Education, 2025)
Motivated by an increasing reliance on subtitles among audiences who may not fully grasp the source language of movies and videos, this study explores subtitle translation, as subtitles have an essential function in facilitating comprehension among audiences. Here, the study focuses on a TED Talk video titled “How Books Can Open Your Mind”. The purpose is to examine the effects of translation errors in subtitles. The study employed a descriptive qualitative method, involving several viewings of the video to attain a comprehensive knowledge of the context. Errors were then identified, categorized, and analyzed using relevant literature and references, including the Kamus Besar Bahasa Indonesia (KBBI). Findings reveal that the identified errors consisted of semantic changes, singular nominal forms, reduction, misinterpretation errors, amplification, and the use of uncommon words. Of these errors, semantic changes were the most frequent, followed by reductions and uncommon words. This study hopes to discover these translation problems in order to better support subtitle translators as well as enhance the viewing experience of target-language audiences in the years to come.